Developing efficient water price in Terengganu, Malaysia: an application of double bounded Contingent Valuation Method (CVM) - Kamaludin, Mahirah; Radam, Alias; Anang, Zuraini; Abdul Aziz, Azlina (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
Population growth is just one of many challenges facing water supply and resource management in Terengganu. The population is rising and driving demand for water and accelerate the degradation of water resources in the state. The total estimated population of Terengganu is around one million people in 2013 and is expected to increase up to two million by 2035. Water industry is just too costly in order to deliver the best to its consumers. Sufficient funding is required to implement various programs and not only left to water providers, who are already burdened by the less remunerative revenue derived from low water rates. The last water tariff reviewed in Terengganu was in 1997, about 17 years ago. At a fundamental level, the facts about good water management are tied to poverty reduction and improved human health. This study utilizes Contingent Valuation Method (CVM) to derive consumers’ willingness to pay (WTP) for improved water services, and based on the WTP value obtained; the aggregate monetary benefits of improving water services for the consumers of Terengganu are estimated. This study will use Logit model in order to analyze primary data gathered during the survey. The findings offer policy recommendations to address the numerous, serious water issues faced by the state. The appropriate water tariff may help the water provider to overcome the problems/challenges in providing better services in the state.